The effects of relocating the reference desk on the circulation desk. Issue 3 (3rd July 2021) - Pfitzinger, Scott
Abstract: In most libraries, the Circulation Desk and the Reference Desk have a complicated relationship. Their physical proximity to each other can affect where patrons go to get assistance and what kinds of questions they ask. Murphy Library at the University of Wisconsin—La Crosse has had the Reference Desk in three different locations in the last five years. In this article an analysis is provided that examines how the different locations have affected the nature and number of questions asked at the Circulation Desk.